Analysis of Flood Hazard Level in Widas Sub Watershed of Nganjuk Regency Using Geographic Information System - Dani Zakiata Fahmi; Titi Rahayuningsih; Vita Ayu Kusuma Dewi; Eko Suwarno (Universitas Islam Raden Rahmat, Malang, 2025)
Widas Subwatershed in Nganjuk Regency is a tributary of the Brantas Subwatershed that often experiences flooding during the rainy season. The data on flooding is still in the form of numbers and tables so it needs to be mapped. The presentation of data in the form of a map is needed so that readers can analyse its distribution and help in mitigation planning against flood disasters. The purpose of this research is to analyse the level of flood hazard in the Widas Subwatershed of Nganjuk Regency and present it in the form of a map. The method used was scoring of 6 flood parameters, namely slope, land elevation, soil type, rainfall, land use, and river density, then weighting with the Analytic Hierarchy Process (AHP) method. The result of this research is that Widas Sub Watershed of Nganjuk Regency is dominated by flood hazard area of 33,375.95 Ha while the flood hazard area is 3,415.55 Ha. Flood hazard areas are found in 28 villages in Gondang, Loceret, Nganjuk, Pare, Sukomoro, and Tanjunganom sub-districts. The flood-prone areas are caused by 4 main factors: low land elevation, Alluvial soil type, residential land use, and the density of the river is very sparse.